Amir Temur's Golden Horse In 1391 Military March (Zien Journal of Social Sciences and Humanities, 2022)
This article gives a brief overview of Jalaliddin Manguberdi's methods of warfare and martial arts. This article is designed to acquaint students of higher and secondary special education institutions with the secrets of martial arts